Meeting information needs of professionals working with otherwise-able students in Nigerian tertiary institutions: Federal College of Education (Special), Oyo as a case study (2006)
This study sought to find out how information sources available to Professionals (Braille experts, Sign Language Interpreters, Audiologists and Speech Therapists) working with the otherwise able students of Federal College of Education (Special), Oyo meet their needs. Survey method was employed in carrying out this study. The unstructured questionnaire was used to collect data and the method of sampling adopted was random sampling technique. The study found written text information such as talking books, sign language textbooks and talking fingers, to be most preferred by the respondents. They also expressed reliance on Internet facilities as a good source of information. Electronic and print media, professional publications and interaction with colleagues are amongst other sources found to be reliable and very useful when seeking information products. It was revealed that the available information System meets the needs of the professionals. However the need for improvement in the observed area of weakness was emphasized as part of recommendation for the library.